Enhancing the framework for financial assistance in the field of physical education and sports through the collaboration of public and private sectors - Altushkin T. I.; Naboychenko E. S.; Knyazeva E. G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to validate the framework for financial backing of physical fitness and sports through a combination of public and private involvement.